CONSIDERATIONS REGARDING CORROSION BEHAVIOR OF ALUMINUM ALLOYS PROCESSED BY FRICTION STIR PROCESSING (FSP) OR SUBMERGED FRICTION STIR PROCESSING (SFSP) (Nonconventional Technologies Review, 2024)
Microstructural stability and submerged properties of aluminium alloys are critical to their integrity and service life in corrosive environments. Submerged friction stir processing (SFSP) and friction stir processing (FSP) have become effective methods for improving the surface characteristics of these alloys, potentially mitigating corrosion-related degradation. This study provides a analysis of the corrosion behaviour of aluminium alloys post-FSP/SFSP processing. The study reveals that FSP/SFSP can significantly refine grain structure, modify the distribution of intermetallic phases, and influence the nature of the oxide film, thereby affecting the corrosion resistance. The findings suggest that optimal FSP/SFSP parameters can be engineered to develop a corrosion-resistant microstructure while preserving the mechanical attributes of the aluminium alloys. This paper contributes to the improvement of knowledge regarding the corrosion processes in FSP/SFSP-treated aluminium alloys in order to use them in various working environments. The alternation in corrosion dynamics as a function of the modified surface conditions could be identified by using electromechanical assays, surface analytical techniques, and microstructural examinations.
Keywords: Corrosion; Alloy Aluminium; FSP; Surface Friction Stir Processing